Kolcaba's theory of comfort in nursing care: an integrative review - Dayse e Silva, Amanda (2023)
Katharine Kolcaba's Theory of Comfort is a mid-range theory that focuses on establishing holistic comfort for the patient and their family, getting them involved in care and creating health-seeking behaviors. In this sense, this study is an integrative review, with the objective of investigating how the Theory of Comfort has been used in the different contexts of nursing practice. After an extensive search, 24 articles published between 2016 and 2021 were analyzed. The use of Theory was observed in several populations, with only one article dealing with comfort with the nursing professional. Seven categories emerged based on the populations in which the Theory was used: elderly, children, women, patients with chronic diseases, immunosuppressed patients, cancer patients and health professionals. It is concluded that Kolcaba's Theory of Comfort can be applied to different populations with different characteristics in the most diverse contexts of care.